2008
DOI: 10.1186/1756-3305-1-40
|View full text |Cite
|
Sign up to set email alerts
|

Oh my aching gut: irritable bowel syndrome, Blastocystis, and asymptomatic infection

Abstract: Blastocystis is a prevalent enteric protozoan that infects a variety of vertebrates. Infection with Blastocystis in humans has been associated with abdominal pain, diarrhea, constipation, fatigue, skin rash, and other symptoms. Researchers using different methods and examining different patient groups have reported asymptomatic infection, acute symptomatic infection, and chronic symptomatic infection. The variation in accounts has lead to disagreements concerning the role of Blastocystis in human disease, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
125
1
12

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(145 citation statements)
references
References 117 publications
4
125
1
12
Order By: Relevance
“…Host genetic factors that can enhance the production of infection-fighting proteins, such as TNF-α may lead to the expression of symptoms in E. histolytica infection (Stanley 2003). A similar pattern is observed in IBS, in which patients who produce (Boorom et al 2008). …”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Host genetic factors that can enhance the production of infection-fighting proteins, such as TNF-α may lead to the expression of symptoms in E. histolytica infection (Stanley 2003). A similar pattern is observed in IBS, in which patients who produce (Boorom et al 2008). …”
Section: Discussionmentioning
confidence: 74%
“…These results are similar to those reported in a study of a French population, which found most human infections to be associated with Blastocystis subtypes 1-3 (L Souppart et al 2009, unpublished observations). Zoonotic subtypes, such as those found in rats and wild birds (subtypes 4, 6, 7), have not been commonly found in patients with chronic infections (Boorom et al 2008). A prior study has found that subtype 2 is more frequently associated with asymptomatic infection (Dogruman-Al et al 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…En los niños es más frecuente asociarlo con diarrea aguda y crónica, dolor y distensión abdominal (1,9). Existe evidencia sobre la mejoría de estos síntomas después del tratamiento con nitroimidazoles (5,10).…”
unclassified
“…Fungal eukaryotes have been implicated as causative agents of diseases such as Inflammatory Bowel Syndrome (IBS) (Blasto-cystis), Inflammatory Bowel Disease (IBD) (fungi), and "leaky gut" syndrome (Candida) [16][17][18]. These diseases, which have become prevalent in western populations, are due to complex changes in the microbial community.…”
Section: Introductionmentioning
confidence: 99%